Sindrom Obstructive Sleep Apnea - William Bahagia; Putu Ristyaning Ayu (CV. Jasa Sukses Abadi, 2020)
Obstructive Sleep Apnea (OSA) is a disorder and part of a complex sleep disorder breathing syndrome. OSA symptoms often occur althought it difficults to detect. If OSA does not get good management, it will cause long-term health problems. OSA is a condition of periodic upper airway obstruction during sleep that causes the breath to stop intermittently, either completely (apnea) or partial (hypoapnea). This condition is occurring in the upper respiratory tract (mainly in the oropharynx) resulting in decreased air flow. OSA symptoms are classified into night symptoms and daytime symptoms. Recurrent episodes of apnea, intermittent hypoxia and sleep fragmentation may affect organ function, especially the central nervous system and cardiovascular system, resulting in changes in metabolic balance. The gold standard for diagnosis of OSA is through a night sleep check with Polysomnography / PSG). The index used to determine the degree of mild-bad OSA is the Apnea-Hypoapnea Index (AHI), which counts the number of obstructive events per hour during sleep and the results of cardiorespiratory monitoring. Management of OSA consists of surgical therapy and non-surgical therapy. Positive airway pressure (PAP) is known to be the gold standard therapy for OSA. This article is a literature study to discuss pathophysiology, risk factors, signs and symptoms, to the handling and prevention of OSA.